A Review on the Application of Voltammetry in the Determination of Various Substances in Fruit Juices - Ortenero, Joseph R.; Dugos, Nathaniel P.; Soriano, Allan N.; T. Borres, Erika Mae; Juan Sing, Ashley Mae T.; A. Pararuan, Mike Dane; R. Tined, Erika Leanne (Applied Science and Engineering Progress, 2022)
Voltammetry is preferred amongst other detection techniques for vitamins and antioxidants because of its selectivity, sensitivity, ease of access, and inexpensive instrumentation. This study aims to assess and evaluate existing studies revolving around the voltammetric determination of vitamins and antioxidants of fruit juices, seeing as they are a rich source of vitamins and antioxidants, to find commonalities and trends over the years. Literature studies found differential pulse voltammetry (DPV) and square wave voltammetry (SWV) to be the most utilized determination method for vitamins and antioxidants, respectively. Electrode performance was also compared between bare and modified electrodes by comparing the limit of detection and recovery rate of each sample. Bare electrodes are found to be suitable for the detection of vitamins by having a high level of detection (LOD) values, but modified electrodes seemed to display enhanced performance when compared to the bare electrode. The optimal pH value of the supporting electrolyte in vitamins is 5.0 ≤ pH ≤ 7.0, while it was found that the optimal pH value for antioxidants was 2.0 ≤ pH ≤ 6.0. Voltammetric determination is highly dependent on the combination of the method, the material used in making the electrode, and the pH of the supporting electrolyte solution.